Converting tourists into evangelists: Exploring the role of tourists' participation in value co-creation in enhancing brand evangelism, empowerment, and commitment. (September 2022) - Nkoulou Mvondo, Gustave Florentin; Jing, Fengjie; Hussain, Khalid; Raza, Muhammad Ali
Abstract: Drawing on the theory of engagement, the present study aims to examine the outcomes of participation in value co-creation in soft sports tourism, specifically hiking. To this end, the current research links the relationship marketing literature to tourism research and formulates a novel framework by incorporating tourists' participation in value co-creation, brand evangelism, customer empowerment, and affective commitment in an integrated conceptual model. Using a quantitative research design, a total of 893 international tourists were surveyed in China. The findings revealed that participation in value co-creation dimensions positively impact brand evangelism, customer empowerment, and affective commitment. Additionally, we found that customer empowerment and affective commitment positively affect brand evangelism. We also confirmed the mediating effect of customer empowerment and affective commitment in bridging the participation in value co-creation and brand evangelism. This study offers valuable insights for brand managers regarding attracting and engaging foreign travelers with their service businesses.